2020
DOI: 10.1002/ece3.6301
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating cetacean body condition; a review of traditional approaches and new developments

Abstract: The ability to accurately gauge the body condition of free‐swimming cetaceans is invaluable in population and conservation biology, due to the direct implications that this measure has on individual fitness, survival, and reproductive success. Furthermore, monitoring temporal change in body condition offers insight into foraging success over time, and therefore the health of the supporting ecosystem, as well as a species’ resilience. These parameters are particularly relevant in the context of widespread and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 145 publications
1
35
0
4
Order By: Relevance
“…7,35,36 Glycogen is a source of carbon, which could increase the C:N ratio 15,35 and therefore result in an overestimated lipid content using the aforementioned calculations. Although empirically measured lipid data do not match the modelled values, it cannot be confidently determined whether this is a limitation of lipid extraction protocols that have been outlined extensively in recent literature 37 or whether it is a model overestimate. This uncertainty means that the true lipid content could lie somewhere between 4% and 14%, and therefore, it is reasonable that chemical lipid extraction has some impact on δ 13 C values.…”
Section: Resultsmentioning
confidence: 91%
“…7,35,36 Glycogen is a source of carbon, which could increase the C:N ratio 15,35 and therefore result in an overestimated lipid content using the aforementioned calculations. Although empirically measured lipid data do not match the modelled values, it cannot be confidently determined whether this is a limitation of lipid extraction protocols that have been outlined extensively in recent literature 37 or whether it is a model overestimate. This uncertainty means that the true lipid content could lie somewhere between 4% and 14%, and therefore, it is reasonable that chemical lipid extraction has some impact on δ 13 C values.…”
Section: Resultsmentioning
confidence: 91%
“…In this study, anthropogenic disturbance leading to the observed foraging disruption was not documented and it is unknown in this case what led to the prolonged stranding event. The ability to detect small changes in body condition has been demonstrated using various techniques 26 and the ability to detect them over a short period of time, as presented here, can be applied to determine the potential impacts of other human-caused interactions. These could include commercial fisheries, chemical pollution, military sonar, and vessel traffic that bring odontocetes into direct conflict with humans and can lead to reduced fitness, disturbance, and disruptions in foraging efficiency 9 , 32 , 32 , 51 , 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Given the difficulty of quantifying feeding requirements and the energetic needs for free-ranging odontocetes, most studies have largely relied on extrapolations 7 with appropriate data for model validation lacking for many species 23 . The use of UASs to estimate morphometric characteristics is well established 24 , 25 and has been used to quantify body conditions 26 for a variety of marine mammals 27 29 . The initial application of UAS technology largely focused on photogrammetry of baleen whales 27 , but it is currently being used for a variety of research applications and species 30 , including odontocetes 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Medidas indiretas permitem estimar a condição corporal quando não é possível pesar os animais (BOYD;BOWEN;IVERSON, 2010). Medidas como a circunferências ao longo do corpo, proporção da circunferência ou larguras pelo comprimento do corpo, circunferência e largura cranial, são as principais abordagens indiretas utilizadas para inferir condição corporal em mamíferos marinhos, em especial por permitirem estimar o peso dos animais a partir de relações morfométricas (BURNETT et al, 2019;CASTRILLON;BENGTSON NASH, 2020;LEMOS et al, 2013;LOCKYER, 2007;MILLER et al, 2012).…”
Section: Condição Corporalunclassified
“…Nos últimos anos, técnicas de fotogrametria aérea baseadas em imagens de drones tem sido uma abordagem amplamente adotada no monitoramento de condição corporal em diversas espécies de mamíferos marinhos (CHRISTIANSEN et al, 2016;FEARNBACH et al, 2018;ALLAN et al, 2019;BURNETT et al, 2019;NOREN et al, 2019). A popularização dos drones deve-se principalmente pela facilidade em controlar o equipamento, por ser uma abordagem não invasiva, bem como pelo custo reduzido do equipamento, mostrando-se mais acessível que o monitoramento aéreo tripulado (ANGLISS et al, 2018;FERGUSON et al, 2018;CASTRILLON;BENGTSON NASH, 2020). Inúmeros modelos estão disponíveis no mercado, que variam quanto a autonomia de voo, tamanho, peso do equipamento, qualidade de câmeras e sensores, entre outros parâmetros, que devem ser selecionados de acordo com a necessidade da pesquisa (COLEFAX; BUTCHER; KELAHER, 2018).…”
Section: Protocolo De Fotogrametria Aéreaunclassified